2023
DOI: 10.1177/23743735231161486
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cystic Fibrosis Primary Palliative Care Intervention: Qualitative Analysis of Patient and Family Caregiver Preferences

Abstract: To prevent or mitigate chronic illness burden, people with cystic fibrosis (pwCF) and their family caregivers need primary (generalist-level) palliative care from the time of diagnosis forward. We used qualitative methods to explore their preferences about a screening-and-triage model (“ Improving Life with CF”) developed to standardize this care. We purposively sampled and interviewed 14 pwCF and caregivers from 5 Improving Life with CF study sites. Thematic analysis was guided by a priori codes using the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The most prevalent physical symptoms are cough, shortness of breath, fatigue, sinus discharge, difficulty sleeping, and pain [1,5,11,12]. Cough, shortness of breath, sinus discharge, and fatigue often are rated as the most severe or distressing symptoms [1,5,11,25]. Additionally, initial data from one trial in 61 adults with CF found that a significant portion of participants reported cough and fatigue as highly distressing (i.e., "quite a bit" or "very much" distressing) at baseline, as well as at 3-, 6-, and 9-month follow-up assessments [26].…”
Section: Epidemiology Of Symptom Burden In Community-dwelling Populat...mentioning
confidence: 99%
“…The most prevalent physical symptoms are cough, shortness of breath, fatigue, sinus discharge, difficulty sleeping, and pain [1,5,11,12]. Cough, shortness of breath, sinus discharge, and fatigue often are rated as the most severe or distressing symptoms [1,5,11,25]. Additionally, initial data from one trial in 61 adults with CF found that a significant portion of participants reported cough and fatigue as highly distressing (i.e., "quite a bit" or "very much" distressing) at baseline, as well as at 3-, 6-, and 9-month follow-up assessments [26].…”
Section: Epidemiology Of Symptom Burden In Community-dwelling Populat...mentioning
confidence: 99%